Coptisine-induced cell cycle arrest at G2/M phase and reactive oxygen species–dependent mitochondria-mediated apoptosis in non-small-cell lung cancer A549 cells - Poorna Chandra Rao; Sajeli Begum; Mahendra Sahai; D Saketh Sriram (Tumor Biology)
This study aimed to explore the effect of coptisine on non-small-cell lung cancer and its mechanism through various in vitro cellular models (A549). Results claimed significant inhibition of proliferation by coptisine against A549, H460, and H2170 cells with IC 50 values of 18.09, 29.50, and 21.60 µM, respectively. Also, coptisine exhibited upregulation of pH2AX, cell cycle arrest at G2/M phase, and downregulation of the expression of cyclin B1, cdc2, and cdc25C and upregulation of p21 dose dependently. Furthermore, induction of apoptosis in A549 cells by coptisine was characterized by the activation of caspase 9, caspase 8, and caspase 3, and cleavage of poly adenosine diphosphate ribose polymerase. In addition, coptisine was found to increase reactive oxygen species generation, upregulate Bax/Bcl-2 ratio, disrupt mitochondrial membrane potential, and cause cytochrome c release into the cytosol. Besides, treatment with a reactive oxygen species inhibitor (N-acetyl cysteine) abrogated coptisine-induced growth inhibition, apoptosis, reactive oxygen species generation, and mitochondrial dysfunction. Thus, the mediation of reactive oxygen species in the apoptosis-induced effect of coptisine in A549 cells was corroborated. These findings have offered new insights into the effect and mechanisms of action of coptisine against non-small-cell lung cancer.